The Origin of the Freedom of Association and of the Right to Strike in Canada. An Historical Perspective - D’Aoust, Claude; Delorme, François (Relations industrielles / Industrial Relations, 1981)
The authors first relate the circumstances surrounding the adoption of an important pièce of our labour legislation and examine the effect of the 1872 legislation on the legal status of union activities.